Microalbuminuria and Cardiovascular Risk Factors in Diabetic Patients from a Medical Office - Agustín Paramio Rodríguez; Gabriel Ignacio Hinojoza Alarcón (Revista Finlay)
Background: the concept of microalbuminuria was introduced as an early marker of diabetic nephropathy and mortality. Microalbuminuria has become a prognostic marker of cardiovascular risk in both diabetics and non-diabetics. Objective: to determine the behavior of microalbuminuria and cardiovascular risk factors in diabetic patients belonging to medical office number 25 of the Presidente Salvador Allende Community Teaching Polyclinic. Methods: a descriptive cross-sectional study was carried out, from a universe of 1125 people, a sample of 62 patients with diabetes mellitus was obtained. The investigation was carried out from January to December 2018. The diagnosis of microalbuminuria was made after two confirmed determinations of the three carried out in a period of 6 months, so there were two groups of patients according to the presence or absence of microalbuminuria, the which was related to cardiovascular risk factors. The descriptive variables were expressed in percentages and the Chi-square statistical method was used to compare the two variables under study. Results: 11.3 % of diabetic patients presented microalbuminuria. 100 % of diabetic patients with positive microalbuminuria suffer from arterial hypertension. 71.43 % of diabetic patients with positive microalbuminuria presented dyslipidemia. 71.43 % of diabetic patients with positive microalbuminuria are obese. Conclusions: in diabetic patients with positive microalbuminuria, the cardiovascular risk factors that were related were: arterial hypertension, dyslipidemia and obesity.